2010
DOI: 10.1007/s00430-010-0165-y
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus-associated pneumonia and bronchiolitis obliterans syndrome in a lung transplant recipient

Abstract: We report the case of a 25-year-old lung and liver transplant recipient who developed respiratory failure. High levels of Epstein-Barr virus (EBV) genome copies were detectable in respiratory tract specimens, while the search for various other viral, bacterial or fungal pathogens remained empty. Post-transplant lymphoproliferative disease was excluded. Due to the rapid progression of respiratory insufficiency, a re-transplantation of the lung was performed. EBV-encoded small RNAs could be demonstrated by in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…181 Rapidly progressive pneumonia and BOS have been described after SOT in association with EBV infection. 182 In addition, some have reported EBV reactivation in pleural fluid and suggested a role for EBV in the development of idiopathic pleural effusions, particularly in immunosuppressed patients. 183,184 An additional respiratory tract condition associated with EBV infection in SOT recipients is laryngeal smooth muscle tumors.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…181 Rapidly progressive pneumonia and BOS have been described after SOT in association with EBV infection. 182 In addition, some have reported EBV reactivation in pleural fluid and suggested a role for EBV in the development of idiopathic pleural effusions, particularly in immunosuppressed patients. 183,184 An additional respiratory tract condition associated with EBV infection in SOT recipients is laryngeal smooth muscle tumors.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Unlike in adults, childhood BO is related more to severe, recurrent respiratory infections (6,7,33,34). Serum ANCAs may also be associated with various microbial infections (4)(5)(6)(7)(8)(9). Given these, we recruited children with mild acute pneumonia as controls.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchiolitis obliterans (BO), a chronic inflammatory process which involves the small airways and typically leads to progressive obliteration of the bronchioles (1), is noted among patients with severe infection, acute lung injury, autoimmune diseases, or in recipients of allogeneic transplantation (2,3). About 1% of children with infectious bronchiolitis may develop BO as a result of microbial respiratory infections (4)(5)(6)(7)(8)(9). Unfortunately, BO in pediatric settings is often misdiagnosed as asthma, classical pneumonia or infectious bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%
“…Epstein-Barr virus (EBV) is a herpesvirus that once contracted remains permanently resident within the host, reactivating from time to time, particularly when there is a diminution of the cellular immune system required for viral control. Reactivation of EBV and shedding of EBV both within the lung allograft and blood occurs in approximately 40-50 % of LTR [43,44], but its reactivation has thus far not been definitively associated with a subsequent increased risk of CLAD [36,45]. A survey of 385 LTR found that having one or more blood samples positive for EBV by PCR increased the risk of subsequent BOS, but the role of immunosuppression on the reactivation of the EBV was not examined [43].…”
Section: Miscellaneous Virusesmentioning
confidence: 99%